The Profile of Crime and Security Conditions in Province DI Yogyakarta (DIY) and Willingness to Pay (WTP) of the People for Reducing Crime Rate - SUPRAYITNO, Bambang; NURSETO, Tejo; FIKRI, Aula A.H.S. (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
The amount of WTP is useful for policy making to reduce crime rates. This study aims to reveal the crime profile of districts/cities in DIY, to know empirically the WTP of the community in DIY for reducing the property crime and non-property crime. It is also to examine how various factors influence on the probability of the willingness to pay. This study used data from samples through a purposive proportional sampling survey of the population of districts/cities in DIY. The Contingent Valuation Method was used to acquire the ability to pay of respondents for reducing crime rates. Various factors that influence the probability of paying were revealed by the econometric approach. The results show that crime intensity in DIY basically follows the trend in Indonesia both in terms of number and crime rate in 2014-2016. The DIY crime rate ranks first in the Java Island and greater than in Indonesia. The average WTP of the population is Rp401.3thousand, so there is a potential fund of Rp1,179.4 billion which can be provided in a year. Individual factors that influence the probability of willingness to pay are the location of the respondent's domicile. According to socio-economic factors, there is no factor that influences the probability. Related to victims of crime, the status of the victim, the type of crime, and who is the offender influence the probability. According to environmental conditions, only the geographical conditions affect the probability. Moreover, only factor in the form of physical impact affects the probability. Population perceptions of payment obligations through tax mechanism to reduce crime and monthly expenses in anticipation of crimes affect the probability of willingness to pay.